Integrating Digital Well-being into MOOCs: A Ten-Year Review of Trends in China's Higher Education - Hu, Xiao; Norman, Helmi; Nordin, Norazah (Yugoslav Journal of Operations Research; Vol 35 No 3 (2025)DO - 10.2298/YJOR240815056H, 2025)
Digital well-being serves as a crucial indicator of the quality and effectiveness of education across countries worldwide. In this context, the rising prominence of Massive Open Online Courses (MOOC) within China's higher education sector warrants further investigation; however, there is a paucity of studies examining how digital well-being contributes to the evolution of MOOC, with limited empirical support available. To address this gap, this study employs literature retrieval and analysis methods, selecting 20 journal articles to offer a comprehensive perspective on the development of MOOC in Chinese higher education. It elucidates background characteristics, developmental trends, theoretical frameworks, and the role of digital well-being in facilitating future advancements in MOOC to resolve value-related challenges encountered during their development process. The findings indicate that the progression of MOOC aligns with digital well-being requirements, suggesting that integration with big data and intelligent systems represents an emerging trend. This synthesis provides novel insights into leveraging digital well-being to enhance MOOC implementation within educational settings in China.